Dielectric relaxation of vegetable-based polyurethane - Sakamoto, W. K.; Kanda, DHF; Andrade, F. D.; Das-Gupta, D. K. (Kluwer Academic Publ, 2003)
Vegetable-based polyurethane (PU) was prepared in the thin film form by spin coating. This polymer is synthesised from castor oil, which can be extracted from the seeds of a native plant in Brazil called mamona. This polymer is biocompatible and is being used as material for artificial bone. The PU was characterised by dielectric spectroscopy in a wide range of frequency (10(-5) Hz to 10(5) Hz) and by thermally stimulated discharge current (TSDC) measurements. The glass transition temperature (T-g=39degreesC) was determined and using the initial rise method the activation energy was found to be 1.58 eV. (C) 2003 Kluwer Academic Publishers.